Comparative Study on Inhibition of Pancreatic Cancer Cells by Resveratrol Gold Nanoparticles and a Resveratrol Nanoemulsion Prepared from Grape Skin - Baskaran Stephen Inbaraj; Leng-Huei Hua; Bing-Huei Chen (MDPI AG, 2021)
Resveratrol, a phenolic compound possessing vital biological activities such as anti-cancer, is present abundantly in grape skin, a waste produced during the processing of grape juice. The objectives of this study were to prepare resveratrol-gold nanoparticles and a resveratrol nanoemulsion from grape skin and study their inhibition effects on pancreatic cancer cells BxPC-3. The spherical-shaped citrate gold nanoparticles (GNPs) and resveratrol-gold nanoparticles (R-GNPs) were, respectively, prepared with a surface plasmon resonance peak at 528 and 538 nm, mean particle size of 20.8 and 11.9 nm, and zeta-potential at −32.7 and −66.7 mV, by controlling an appropriate concentration of citrate/resveratrol and gold chloride as well as stirring time and temperature. The resveratrol nanoemulsion, composed of soybean oil, Tween 80, and sucrose fatty acid ester in glycerol and water, possessed a high storage stability with a mean particle size of 14.1 nm, zeta-potential of −49.7 mV, and encapsulation efficiency of 95.5%. An antiproliferation study revealed that both R-GNPs and resveratrol nanoemulsion could effectively inhibit the growth of pancreatic cancer cells BxPC-3, with the latter showing a higher inhibition effect. Western blot analysis implied that both can down-regulate expressions of cyclin A, cyclin B, CDK1, and CDK2 and up-regulate expressions of p53 and p21, accompanied by enhancing cytochrome C expression, decreasing BcL-2 expression, increasing Bax expression, and leading to the elevation of caspase-8, caspase-9, and caspase-3 activities for cell apoptosis execution. Future research is needed to study the inhibition of pancreatic tumors in vivo by R-GNPs and resveratrol nanoemulsions.